An Epistemology of Revelation - Arpad Szakolczai (Religions)
The aim of this article is to approach the epistemology of revelation through the approach of political anthropology. It departs from Max Weber’s distinction between ordinary and out-of-the-ordinary situations, which led to his idea of charismatic power. This article complements the Weberian perspective by introducing the anthropological term “liminality” for such situations, as well as the term “trickster” for figures who have a specific affinity for appearing in such situations, creating havoc instead of offering a solution. Ordinary knowledge does not apply to liminal void situations of incommensurability; incommensurable knowledge can be gained by magic and religion. Magic forces the transcendent and claims to produce effects, while religion is based on revealed knowledge, the validity of which is established by trust. Under particularly anguishing liminal conditions, the hardly tolerated practitioners of magic might gain positions of power. An important such example is offered by Persian Magi. Turning to the present, modern rationalism, with Bacon and Descartes, undermined both ordinary and revealed knowledge. The possible relevance of revealed knowledge in contemporary times is discussed through the related phenomena of apocalyptic expectations and Marian apparitions.